2018
DOI: 10.3847/1538-4357/aaa3ff
|View full text |Cite
|
Sign up to set email alerts
|

A Quasi-periodic Fast-propagating Magnetosonic Wave Associated with the Eruption of a Magnetic Flux Rope

Abstract: Using high temporal and high spatial resolution observations taken by the Atmospheric Imaging Assembly onboard the Solar Dynamics Observatory, we present the detailed observational analysis of a high quality quasi-periodic fastpropagating (QFP) magnetosonic wave that was associated with the eruption of a magnetic flux rope and a GOES C5.0 flare. For the first time, we find that the QFP wave lasted during the entire flare lifetime rather than only the rising phase of the accompanying flare as reported in previo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 66 publications
2
47
0
2
Order By: Relevance
“…Similar observational studies were carried out by e.g. Shen & Liu (2012, the projected phase speed of ∼ 834 km s −1 and mean period of 25-83 s), Yuan et al (2013, 600-735 km s −1 and 38-58 s), Nisticò et al (2014, ∼ 1000 km s −1 and 60-80 s), and in a more recent work by Shen et al (2018Shen et al ( , 875-1485 km s −1 and 75-160 s).…”
Section: Introductionsupporting
confidence: 77%
“…Similar observational studies were carried out by e.g. Shen & Liu (2012, the projected phase speed of ∼ 834 km s −1 and mean period of 25-83 s), Yuan et al (2013, 600-735 km s −1 and 38-58 s), Nisticò et al (2014, ∼ 1000 km s −1 and 60-80 s), and in a more recent work by Shen et al (2018Shen et al ( , 875-1485 km s −1 and 75-160 s).…”
Section: Introductionsupporting
confidence: 77%
“…Previous observational studies indicated that the excitation of QFP waves include several possible mechanisms, including 1) the nonlinear energy-releasing processes in the magnetic reconnection process of flares (e.g., Liu et al 2011;Shen & Liu 2012b;Shen et al 2013aShen et al , 2018c, 2) the leakage of photospheric pressure-driven oscillations into the corona (e.g., Shen & Liu 2012b), and 3) the dispersive evolution of an initially broad-band disturbance in inhomogeneous medium (e.g., Nisticò et al 2014;Shen et al 2018b,d). For the present case, by analyzing the periods of the associated flare we find that the periods of the QFP wave and the associated flare showed large difference.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…So far the driv-⋆ E-mail: ydshen@ynao.ac.cn ing mechanism of QFP waves is still unclear. Recent observations indicated that QFP waves often share one or more periods with the accompanying flares (e.g., Liu et al 2011Liu et al , 2012Shen & Liu 2012b;Shen et al 2013aShen et al , 2018c, thus the nonlinear energy releasing processes in magnetic reconnections are thought to be the possible exciter (e.g., Ofman & Sui 2006;Kliem et al 2000;McLaughlin et al 2012). Besides, the leakage of photospheric oscillations to the corona (e.g., Shen & Liu 2012b) and the dispersively evolution of an initial broad-band disturbance (e.g., Nisticò et al 2014;Shen et al 2018b,d) are also possible drivers for QFP waves.…”
Section: Introductionmentioning
confidence: 99%
“…QFP波时常在传播过程中表现出明显的波动效 应. 比如, 与强磁场结构作用发生明显的折射效应进而 改变传播方向 [23,94] ; 沿闭合磁力线传播时, 波前在磁力 线另一端被反射并导致闭合磁环的振荡等 [19,45,133] .…”
Section: Qfp波最早出现位置离耀斑中心的距离通常>100unclassified
“…QFP波. 大多数QFP波的激发可能与引发耀斑的磁重联 过程中的非线性物理过程密切相关 [21,23,25,137,139] , 例如 电流片中等离子体团的分裂、合并和喷射 [140,141] 以及 振荡重联等 [142] . 同时, 部分观测结果显示, 太阳爆发扰 动在非均匀介质中通过色散式演化 [24,94,95] , 而光球压 力模向上泄漏到日冕 [21,22]…”
Section: 荡相关 不会激发准周期波; 而其余3种机制都可激发unclassified